Bentuk Penyajian Tari Marandang Sanggar Pituah Bundo Kota Payakumbuh - Syifa Tiara Vania; Susmiarti Susmiarti (Institut Nalanda, 2024)
This study aims to describe and reveal the form of presentation of Marandang Dance at the Pituah Bundo Studio, Payakumbuh City. The type of research is qualitative research with a descriptive analysis method. The research instrument is the researcher himself and is assisted by supporting instruments such as recording tools, recording tools Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The steps to analyze the data are data reduction, data display and drawing conclusions. The results of the study in general show that the Marandang Dance at the Pituah Bundo Studio is carried out in groups. The dancers consist of male dancers and female dancers. This dance is only performed at major events and art exhibitions in Payakumbuh City and outside Payakumbuh City. The duration of the performance is approximately ten minutes. The elements of this form of dance presentation are as follows: (1) Tapuak Mamuta Movement, Sambah Movement, Open Hand Movement, Swing Lambai Movement, Ambek Bukak Movement, Mambukak Furnace Movement, Puta Tusuak Movement, Cross Hand Movement, Wood Massage Movement, Material Malatakan Movement, Maaduak Kaali Movement, Balajan Lenggok Movement, Maayun Swing Movement, Ambiak Latak Movement, Lenggok Dulang Movement, Sanduak Randang Movement. (2) The Marandang Dance Floor Pattern uses a straight line and curved pattern. (3) The makeup used is beautiful makeup and dashing makeup. The clothing used by female dancers is Baju Kuruang. Meanwhile, the clothing used by male dancers is the Taluak Balango Shirt. (4) The properties used in this Marandang dance are cauldrons, kacik, sanduak, katidiang, trays, torches, firewood and Marawa. (5) Music accompaniment using musical instruments such as talempong, gandang, Tasa, Bansi, Saluang, Bass and keyboards.